Den politiske presse - En analyse af danske avisers politiske orientering - Hjarvard, Stig (Journalistica, 2007)
Contemporary media and press theory (e.g. Cook: “Governing with the News”, Hallin & Mancini: “Comparing Media Systems”) tend to agree on the decline of the political press. As news media get more commercial, their political influence is based on their role as independent journalistic institutions and not through ties to the political parties. However, recent developments in the Danish newspaper market seem to contradict this assumption. As free newspapers challenge older morning papers, we simultaneously experience the expansion of a politically neutral and purely commercial press, and a repoliticized press giving more prominence to opinions and values. Political parallelism between part of the press and the political institutions seems to persist.